Relationship among Sports Participation, Self-Perception and Gender Role Orientation of Adolescent Female Students in Kwara State, Nigeria - Babatunde Samson Adebayo (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
This study examined the relationship among sports participation, self-perception and gender role orientation of adolescent female students in Kwara State. Descriptive survey design was adopted for the study. 240 respondents were sampled from public secondary schools in Kwara State through simple random sampling technique; eight (8) public secondary schools were selected. Stratified and proportionate sampling techniques were used to select 20% of students by class. The research instrument was a self-structured close ended questionnaire. The data collection was conducted by the researcher and three (3) research assistants. Three null hypotheses were tested using Pearson's Product Moment Correlation (PPMC) statistic at 0.05 alpha level. The findings revealed no significant relationship between self-perception and sports participation, there was significant relationship between gender role orientation and sports participation. Also, there was significant relationship between social interaction and sports participation among the adolescent female students. The study recommends that the concept of sports should be promoted among the students while female students should be given equal opportunity in sports as their male counterpart. Also all students should be encouraged to participate in sports in order to promote social relationship with other students.